Toothbrushing Behavior and The Incidence of Dental Caries In Children - Wardani, Ika Kusuma; Dewi, Renie Kumala; Adhani, Rosihan; Garcia, Aprilia (Jurnal Berita Ilmu Keperawatan, 2024)
One of the most common children's dental health problems is dental caries. Childhood is the beginning of behavior formation, therefore it is hoped that parents can educate their children to behave correctly in maintaining healthy teeth and mouth.This research used descriptive survey research methods. The design of this research is cross sectional. The research was conducted at MIS Cempaka Putih and MIS Sungai Baru, South Kalimantan. The population in this study was all students in grades 4-6 at MIS Cempaka Putih and MIS Sungai Baru, there are 41 people. The sampling technique in this research used the total sampling method. The variables in this study are children's dental health behavior and the DMF-T index. The data that has been collected will be processed through editing, coding, tabulation and descriptive data analysis. This research was conducted at MIS Cempaka Putih and MIS Sungai Baru Banjarmasin in February 2022. Respondents were 10-12 years old. The dental health behavior of children in the good category was 14 people (34.15%), 15 people (36.58%), and 12 people less (29.27%). DMF-T index in the very high category was 3 people (7.32%), high was 4 people (9.76%), medium was 18 people (43.90%), low was 13 people (31.70%), and very low 3 people (7.32%). Based on the research results, it can be concluded that the dental health behavior of children in grades 4-6 at MIS Cempaka Putih and MIS Sungai Baru is mostly adequate for 15 people (36.58%). The class 4-6 DMF-T index in MIS Cempaka Putih and Sungai Baru has an average value of 3.5, including the medium category.